Investigação do potencial energético de dispositivos coletores de energia de estradas pavimentadas - Conceição, Leonardo Gabriel Carvalho da Costa (Universidade Federal de São Carlos, 2019)
The search for alternative sources of energy is a recurring theme in research due to the growth of world energy demand. The development of energy harvesting techniques and devices is required. This work focused on studying two energy energy harvesting devices applied on pavemented roads. Speciﬁcally, it was focused on studying one device based on hydraulic elements and the other based on electromechanical elements, of completely different natures. For these were developed their mathematical and computational modeling (in the software MATLAB/SIMULINK) in order to collect results that would allow to investigate and compare their energy potentials. It was concluded that the electromechanical road pavement energy harvesting device has higher energy potential, through the analysis of the simulation results of the computational models.
Investigation of the energetic potential of energy harvesting systems for paved roads
Keywords: Coletores de energia; Veículos; Sistemas hidráulicos; Sistemas eletromecânicos; Energy harvesting; Vehicles; Roads; Hydraulic systems; Electrome-chanical systems; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS